2022-RA-605-ESGO Long term quality of life after chemotherapy among rare ovarian cancer survivors: the national gineco case-control Vivrovaire Rare Tumors study. (20th October 2022) - Joly, Florence; Ray-Coquard, Isabelle Laure; Floquet, Anne; Lefèvre-Arbogast, Sophie; Selle, Frederic; Berton, Dominique; Frank, Sophie; Rouge, Thibault De La Motte; Kalbacher, Elsa; Provansal, Magali; Lortholary, Alain; Orfeuvre, Hubert; et al.
Abstract : Introduction/Background: Treatments of non-epithelial rare germ cell tumors (GCT) and sex cord stromal tumors are associated with long survival. They mainly include conservative surgery plus chemotherapy (CT) [bleomycin, etoposide and cisplatin (BEP)] depending on stage and prognostic factors. As reported in testicular cancer survivors, BEP may induce late side effects with negative impact on quality-of-life (QOL). The French Rare Malignant Gynecological Tumors (TMRG)/GINECO case-control study assessed long term QOL among survivors treated with BEP as compared to age-matched healthy women (HW). Methodology: Non-epithelial ovarian cancer survivors (nEOCS), cancer-free ≥2 years after end of treatment, were identified from the INCa French Network for TMRG. HW were issued from the 'Seintinelles' research platform. QOL (FACT-G/FACT-O), chronic fatigue (MFI), anxiety/depression (HADS), insomnia (ISI), neurotoxicity (FACT/GOG-NTX), cognition (FACT-COG) and sexuality items (from FACT-O OCS) were compared between nEOCS and HW. A minimal 5% difference of scores between groups was considered as clinically relevant. Results: 144 nEOCS (including 112 GCT) plus 144 age-matched HW were enrolled (mean age at inclusion: 38; 60% <40). Median delay from the end of treatments to inclusion was 6 yrs. At inclusion, 42% of nEOCS were menopausal versus 17% of HW (p<0.001). General and ovarian QOL, fatigue, anxiety/depression and insomnia scores were similar between nEOCS and HW. Although nEOCS reported clinically significant (6%) better social functioning (p=0.006), nEOCS reported more perceived cognitive impairment than HW (31 vs 14%, p<0.001) and clinically significant (8%) neurotoxicity (p<0.001). They also reported less interest in sex (35% vs 55%, p<0.001) and more concern of childlessness (31% vs 13%, p=0.007) than HW, whatever the menopausal status. Conclusion: 6 yrs after BEP CT, most of nEOCS reported similar global QOL as HW, but they experienced more often premature menopause, some late side effects on cognition, neurotoxicity and sexuality that may impact their daily life.